The Dispensable Roles of X-Linked Ubl4a and Its Autosomal Counterpart Ubl4b in Spermatogenesis Represent a New Evolutionary Type of X-Derived Retrogenes - Yu, Changping; Diao, Runjie; Khan, Ranjha; Deng, Cheng; Ma, Hui; Chang, Zhijie; Jiang, Xiaohua; Shi, Qinghua (Frontiers in Genetics, 2021)
X-derived retrogenes contribute to genetic diversity in evolution and are usually specifically expressed in testis and perform important functions during spermatogenesis. Ubl4b is an autosomal retrogene with testis-specific expression derived from Ubl4a, an X-linked housekeeping gene. In the current study, we performed phylogenetic analysis and revealed that Ubl4a and Ubl4b are subject to purifying selection and may have conserved functions in evolution. Ubl4b was knocked out in mice using CRISPR/Cas9 genome editing technology and interestingly, we found no alterations in reproductive parameters of Ubl4b-/- male mice. To get insight into whether Ubl4a could compensate the absence of Ubl4b in vivo, we further obtained Ubl4a-/Y; Ubl4b-/- mice that lack both Ubl4a and Ubl4b, and the double knockout (dKO) mice also displayed normal spermatogenesis, showing that Ubl4a and Ubl4b are both dispensable for spermatogenesis. Thus, through the in vivo study of UBL4A and UBL4B, we provided a direct evidence for the first time that some X chromosome-derived autosomal retrogenes can be unfunctional in spermatogenesis, which represents an additional evolutionary type of X-derived retrogenes.